Zinc-/copper-substituted dicalcium silicate cement: advanced biomaterials with enhanced osteogenesis and long-term antibacterial properties. Issue 5 (15th January 2020) - Zhang, Feng; Zhou, Mingming; Gu, Weizhong; Shen, Zheng; Ma, Xiaohui; Lu, Fengling; Yang, Xianyan; Zheng, Youyang; Gou, Zhongru
Abstract : Dicalcium silicate (C2 S) cements doped with Zn or Cu exhibited appreciable osteogenic activity and prolonged antibacterial potential in comparison with C2 S cement. Abstract : The development of bioactive Ca-silicate-based cements which may simultaneously suppress infection is promising for periapical therapy or alveolar bone defect repair. While these treatments are usually effective in the short term, many of these cements have not been designed to have an affinity with dental tissue in a prolonged anti-infectious manner and are only high alkaline in the early stages. This can lead to less favorable long-term outcomes, such as in bone repair or secondary therapy. Inspired by the strong antibacterial activity of zinc and copper ions, we developed a nonstoichiometric dicalcium silicate (C2 S) substituted by 5% or 10% Zn or Cu to endow it with appropriate multifunctions. It was found that the foreign ion substitution could inhibit free CaO content and increase the pH value in the initial ∼6 h. The C2 S cement only showed antibacterial activity in the early stage (6–72 h), but the C2 S displayed appreciable long-term antibacterial potential against P. aeruginosa, E. faecalis and E. coli (>6 h) and S. aureus (>72 h). Moreover, the enhanced new bone regeneration by Zn substitution in C2 S was confirmed in a maxillofacial bone defect model in rabbits. The increases in new bone formation adjacent to C2 S–10Zn and C2 S after 16 weeks of implantation were 32% and 20%, respectively. And the Tb.N values in the C2 S–10Zn and C2 S–10Cu groups (∼5.7 and 4.9 mm −1 ) were over two-fold higher than in the C2 S group (∼2.0 mm −1 ). It is considered that Zn- or Cu-substitution in C2 S is promising for applications to infectious bone repair.